2015
DOI: 10.1002/2015gl064671
|View full text |Cite
|
Sign up to set email alerts
|

Controls on 231Pa and 230Th in the Arctic Ocean

Abstract: The distributions of 230Th and 231Pa in the Arctic Ocean are not well understood. In order to examine the Arctic 231Pa/230Th system and therefore to shed light on the future use of Arctic sedimentary 231Pa/230Th, we developed a 2‐D scavenging model modified from an Atlantic model. Tuned with reasonable parameters that are consistent with Eurasian Basin geographic settings, the model can reproduce most of the features of the 230Th and 231Pa water column profiles as well as the sedimentary 231Pa/230Th distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…231 Pa measurements were also performed in MC‐11, allowing some comparison with the Lomonosov sequence. The AR( 231 Pa xs / 230 Th xs ) ratios near core top at both sites (from 0.04 to 0.06; supporting information Table S3 and Not and Hillaire‐Marcel ()) are in the range of values reported in earlier studies by Moran et al () and modeled by Luo and Lippold (), but in the lower range of values when compared with data in Hoffmann et al (). As a few centimeters are missing on top of the shallower core K‐030 from Lomonosov, 231 Pa and 230 Th excesses in its Holocene section are unconstrained.…”
Section: Discussionsupporting
confidence: 62%
“…231 Pa measurements were also performed in MC‐11, allowing some comparison with the Lomonosov sequence. The AR( 231 Pa xs / 230 Th xs ) ratios near core top at both sites (from 0.04 to 0.06; supporting information Table S3 and Not and Hillaire‐Marcel ()) are in the range of values reported in earlier studies by Moran et al () and modeled by Luo and Lippold (), but in the lower range of values when compared with data in Hoffmann et al (). As a few centimeters are missing on top of the shallower core K‐030 from Lomonosov, 231 Pa and 230 Th excesses in its Holocene section are unconstrained.…”
Section: Discussionsupporting
confidence: 62%
“…For example, although Pyrgo species are tolerant to very irregular and reduced food supply and thus may persist during short episodes of very low food fluxes [ Struck , ; Linke and Lutze , ], hyaline benthic species such as Elphidium excavatum are also well adapted to a very wide range of food supply, temperature, and salinity [ Vilks , ; Linke and Lutze , ]. A possible further challenge to this scenario is also the interpretation of Pa/Th data from the Central Arctic Ocean, which have been used to suggest a centennial scale replacement for deep waters in the Central Arctic Ocean during the past 35 kyr [ Hoffmann et al ., ]; notwithstanding, however, the possibility that boundary scavenging in areas with higher particle fluxes may have been an important sink for Pa [ Hoffmann et al ., ; Luo and Lippold , ]. Excluding the miliolid‐based 14 C ventilation ages, there is a general trend toward increasing ventilation ages over HS1, reaching maximum values (P‐A = ~800 14 C years, B‐A = ~1800 14 C years, and B‐P = 1000 14 C years) at 15 ka, just prior to the onset of the Bølling‐Allerød (BA) interstadial (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Not many studies have reported 231 Pa/ 230 Th ratios slightly exceeding the production ratio (e.g. Luo and Lippold, 2015). The overall low 231 Pa/ 230 Th ratios casted some doubts on mechanisms driving the boundary scavenging in the Arctic Ocean.…”
Section: Introductionmentioning
confidence: 99%